2014
DOI: 10.1002/jor.22709
|View full text |Cite
|
Sign up to set email alerts
|

The role of subscapularis muscle denervation in the pathogenesis of shoulder internal rotation contracture after neonatal brachial plexus palsy: A study in a rat model

Abstract: We assessed the role of subscapularis muscle denervation in the development of shoulder internal rotation contracture in neonatal brachial plexus injury. Seventeen newborn rats underwent selective denervation of the subscapular muscle. The rats were evaluated at weekly intervals to measure passive shoulder external rotation. After 4 weeks, the animals were euthanized. The subscapularis thickness was measured using 7.2T MRI axial images. The subscapularis muscle was then studied grossly, and its mass was regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This sarcomere elongation correlated with contracture severity, and indicates fewer sarcomeres in series in the whole muscle (22), or impaired longitudinal whole muscle growth. This finding that neuromuscular contractures are caused by muscle that has failed to grow normally in length as a direct result of denervation, independent of the mechanical environment, has been replicated in subsequent animal (23,24), clinical (25)(26)(27), and computational analysis (28,29) studies. Therefore, our previous data indicate that defects in muscle growth are the initiating cause of contractures.…”
Section: Introductionmentioning
confidence: 72%
“…This sarcomere elongation correlated with contracture severity, and indicates fewer sarcomeres in series in the whole muscle (22), or impaired longitudinal whole muscle growth. This finding that neuromuscular contractures are caused by muscle that has failed to grow normally in length as a direct result of denervation, independent of the mechanical environment, has been replicated in subsequent animal (23,24), clinical (25)(26)(27), and computational analysis (28,29) studies. Therefore, our previous data indicate that defects in muscle growth are the initiating cause of contractures.…”
Section: Introductionmentioning
confidence: 72%
“…Through a murine model of neonatal brachial plexus injury (NBPI) pioneered in our laboratory, we previously demonstrated that contractures result from impaired longitudinal growth of muscle denervated during a critical window of neonatal development. [8][9][10][11] The contribution of impaired longitudinal muscle growth to contracture formation has been replicated by others using similar rodent models, 12,13 and is further supported by clinical studies in infants and children. 14,15 While the regulation of muscle length and its contribution to skeletal muscle growth/development are not well characterized, prior studies have posited a role for muscle stem cells (satellite cells) in governing the length of a muscle.…”
Section: Introductionmentioning
confidence: 75%
“…These contractures severely impede mobility of the affected limb, ultimately resulting in dysfunction and disability [4]. Previous work in animal and clinical studies has revealed that contractures are caused by impaired longitudinal growth of denervated muscles [5][6][7][8][9][10][11][12], which is driven by elevated levels of muscle proteasome activity [13][14][15]. It is thus imperative to decipher mechanistic links between denervation, muscle proteostasis, longitudinal muscle growth, and contractures in order to identify novel avenues for contracture prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%